The impact of forest fire on air-quality and visibility in Palangka Raya - Sumaryati Sumaryati; Nani Cholianawati; Asri Indrawati (Universitas Sebelas Maret, 2019)
It has been analyzed impact of forest fire on the air quality using PM10 parameter and visibility during 2000 – 2014 in Palangka Raya, Central Kalimantan province. Palangka Raya is an affected forest fire area with a monsoonal rainfall type which has one peak of the rainy season in January and one peak of the dry season in August. Drought condition has an impact on rising forest fire intensity causes increasing of PM10 concentration and decresing of visibility in July to November moreover when there is an El Niño phenomenon. The result of PM10 analysis shows that the air quality index in Palangka Raya during December - June is in a good level category and still below the ambient air quality standard with an average concentration of 19 µg/m3. The impact of forest fire on declining air quality due to increasing of PM10 concentration occurred in July – November with an average concentration rising of 129 µg/m3. The El Niño phenomenon rises the PM10 concentration due to increasing of forest fires, but the increasing of PM10 is not comparable to the strength of El Niño, because of combustion condition and and human activities that play a role in forest fires. The worst impact of El Niño occurred in 2002, although the El Niño strength was only moderate, which is a half the time from July to November Palangka Raya covered air quality with dangerous levels with PM10 concentrations of more than µg/m3. A high PM10 concentration environment reduces the visibility significantly, which is visibility in the no fire condition about 8 km, but when the huge forest fire the visibility drops to 0.1 km.